Daily Good-Deed Habituation and Teacher Role Modelling as Quantitative Predictors of Students’ Religious Character: An Empirical Study at SMKN 6 Berau, Indonesia - Syamsidar; Benny Prasetya; Muhammad Alfi Syahrin; Khamam Khosiin (PT. Caesarindo Triloka Persada, 2026)
The development of students’ religious character is a central goal in vocational secondary education, yet many students exhibit suboptimal religious behaviours, including low discipline and limited social awareness. This study investigates the influence of daily good-deed habituation (One Day One Good Deed, ODOGD) and teacher role modelling on students’ religious character at SMKN 6 Berau, Indonesia. Employing a quantitative correlational design, data were collected from 165 students using validated questionnaires and analysed through multiple linear regression. Results indicate that both the ODOGD programme (β = 0.195, p = 0.005) and teacher role modelling (β = 0.732, p < 0.001) significantly contribute to the development of students’ religious character. Teacher role modelling emerged as the strongest predictor. The combined influence of both variables explains 82.5% of the variance in students’ religious character. These findings highlight that consistent daily habituation of positive actions, supported by teachers’ exemplary behaviour, effectively fosters moral and religious values in students. The study provides empirical evidence for integrating structured character education programmes and teacher exemplars into school curricula to strengthen holistic student development.